Parenchymal-stem segmental portal vein embolization as a stage of preparation of patients with malignant liver tumors to surgical treatment - V. A. Kondratiuk (Medičnì Perspektivi)
Article presents results of the study of the parenchymal-stem segmental portal vein embolization (PVE) efficacy, performed in patients with advanced malignant liver tumors and a marginally small hepatic residue as preoperative preparation. The technical efficiency of PVE was studied by comparing 218 patients who underwent parenchymal-stem segmental modification of PVE (main group) and 124 patients who underwent other PVE modifications (comparison group). It was noted that in the main group PVE was followed with 6.1% lower percentage of complications (6.0% versus 12.1%), which allowed to perform a successful technical EEV in 205 (94.0% main and 124 (83.9%) the comparison group. Radical liver resection was performed in 286 (83.6%) of the total amount of patients, 192 (88.1%) – in the main group, and 94 (75.8%) – in the comparison group. Thus, the introduction of parenchymal-stem segmental embolization of the portal vein allowed to expand the range of operability of patients with advanced malignant liver tumors by 12.3% (from 75.8% to 88.1%).